Cysteine proteases of pathogenic organisms - Robinson, Mark W.; Dalton, John P. (Springer eBooks., 2011)
Cystene proteases expressed by pathogenic organisms play key roles in virulence including host entry, feeding and suppression of host immune responses. This book gives comprehensive coverage to all aspects of pathogen cysteine proteases and brings together numerous scientific advances which have been made over many years. Thus, the biochemistry, molecular biology and structure?function relationships of these important pathogen enzymes are covered in detail. Written by leading researchers from Europe, Australia and North America, this book is essential reading for students and professionals interested in human medicine and infectious disease research.